Pembangunan Kakas Bantu Perhitungan Kualitas Kode (Quality Rate) menggunakan Metrik Perangkat Lunak - Odhia Yustika Putri; Bayu Priyambadha; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
A good quality software is usually understood as a lack of errors within the software. The previous study entitled â€œTowards a Reliable Identification of Deficient Code with a Combination of Software Metricsâ€ has been done by Beranic in 2018 and showed the use of combination of 8 object-oriented software metrics to identify deficient code in certain software. The deficient code detection can be used to calculate the quality rate. However, the calculation of deficient code and quality rate are done separately. To overcome this problem, a tool is made for the calculation of quality rate with a combination of software metrics. This tool was built using Software Development Life Cycle (SDLC) Waterfall method and coded in Java. This tool runs on a desktop platform and use Java project as its input. Requirement engineering process in this tool produced 3 functional requirements and 1 non-functional requirement. The design is in object-oriented and produced 1 class diagram, 3 sequence diagrams, 5 algorithms, and 3 user interface design. The design is develop using JavaFX and ASTParser library. The outcome of the white-box and black-box tests indicate that this tool has a validation percentage of 100%.